Caribbean Report 14-02-1992 - Goffe, Leslie (anchor); Norton, Michael (correspondent); Walker, Herbert (interviewee); Fawcett, Tim (correspondent); Joseph, Maynard (interviewee); Water, Frank (interviewee) (The British Broadcasting Corporation, 1992)
Haitian lawmarkers call on the President of the Senate for a date and venue to be announced within the next 72 hours for the next rounds of talks with the OAS. United States express concerns on reports circulating that people trying to leave Haiti are being persecuted. After fears are expressed by the Dominican Republic on the ability to provide adequate security for ousted Haitian President Jean Bertrand Aristide, he declines to apeak at a scheuled meetngin Haiti, while reports circulate on the real reason for not wanting him to speak. An OAS representative withdraws from attendance to a UN Caribbean and Latin group meeting on the crisis in Haiti. The OECS reviews the tariff ceiling in the Common External Tariff. General Secretary of the Barbados Workers Union says hte regions politicians are misjudging the desire for integration and Caribbean Banana Producers are seeking assurances from the European Community that their guaranteed markets under the Lome Convention will not be destroyed by the Introduction of the Single European Market.
1. Headlines (00:00-00:42)
2. Report on the call by Haitian lawmakers to the President of the Senate to arrange the next rounds of talks with the OAS, and calls for a date and venue within the next 72 hours. Michael Norton reports from Port-au-Prince on whether the law makers were serious and on the violence in Haiti (00:43-03:35)
3. Report on the concerns by the United States about reports that people trying to leave Haiti are being persecuted. U.S. says they would be sending more staff to the embassy in Haiti to monitor the situation, as well as asking the Haitian authorities about the detention of two journalist, one employed by the BBC (03:36-04:06)
8. Report that ousted Haitian President, Jean Bertrand Aristide would not be attending the scheduled ACP-EC meeting in the Dominican Republic (13:36-14:09)
Keywords: Haiti -- Presidents.; Haiti--Politics and government.; Organisation of American States.; Refugees -- Haiti.; Aristide, Jean-Bertrand.; Tariff structure.; Taxation -- Caribbean Area.; Banana trade -- Caribbean Area.; Banana trade -- Dominica.; Haitian refugees -- Violence.; Repatriation -- Haitian refugees.; Barbados Workers Union.